Inside adobe(R) photoshop(R) 5.5 - Bouton, Gary David; Kubicek, Gary.; Bouton, Barbara Mancuso ([S.l.] : New Riders Publishing, 2000)
For courses in Photoshop. Inside Adobe Photoshop 5.5 teaches Photoshop's capabilities through step-by-step techniques that are specifically designed to create knowledge and effects that readily transfer to other uses of image editing in Photoshop. Inside Photoshop 5.5 offers tips, tricks, and invaluable high-end techniques that result in top quality professional images.